Formulation of High Protein and Fiber Soy-Based Chicken Nugget - Baba, Carollynna; Hatijah Basri, (Enhanced Knowledge in Sciences and Technology, 2024)
Chicken nuggets are a popular processed meat product composed of bite-sized, breaded and fried or baked pieces of chicken. They are usually made from processed chicken meat, often containing a combination of chicken breast, skin, and other ingredients. Due to health concerns, chicken nugget was decreased in popularity because of the unhealthy ingredients, additives and processing method during the production. To address this, four soy-based chicken nugget formulations were developed, by focusing on protein enhancement and dietary fiber while reducing fat content at the same time. These formulations varied in the percentage of Okara used: 30 %, 50 %, 60 %, and 80 %. The comparison between four formulations of soy-based chicken nuggets and two commercial nuggets were conducted during this study. The comparison includes characterization of chicken nuggets such as pH, moisture content, texture, and color (L* a* b* values). Results showed that all the values significantly (p